Peran Kepemilikan Manajerial Memoderasi Tingkat Hutang, Ukuran Perusahaan, Arus Kas Operasi Terhadap Persistensi Laba - Salam, Muhamad Robi; Amin, Muhammad Nuryatno (Politeknik Ganesha Medan, 2024)
This study uses management ownership as a moderating variable to examine the effects of debt levels, firm size, and operating cash flow on earnings persistence. Quantitative approaches are employed in this study. Up to 80 samples were selected via purposive selection, with the population of this study consisting of industrials sector companies listed on the Indonesia Stock Exchange in 2019–2022. Multiple linear regression analysis models and moderated regression analysis (MRA) were used for the hypothesis testing, with the moderator variables being tested. The results of this research based on partial testing (t test) probability value of the debt level variable is 0.008. The firm size variable is 0.032. The operating cash flow variable is 0.160. The managerial ownership variable is 0.014. The degree of debt and management ownership have an interaction variable of 0.016. The interaction variable between firm size and managerial ownership is 0.010. Additionally, managerial ownership and operating cash flow interact with a coefficient of 0.132. Known that debt levels and firm size have positive effect on profit persistence, while operating cash flow has no effect on profit persistence. The moderating effect of managerial ownership can amplify the favorable impact of debt levels on earnings persistence. However, the favorable impact of company size and operating cash flow on earnings persistence cannot be amplified by managerial ownership